Development and Assessment of Copper Nanoparticles Synthesized from Wild carrot. Leaf Extract for Cancer Therapy - Nandal, Rimmy; Attri, Amit; Dhiman, Priya; Rathee, Varsha; Khandodiya, Vikash; Nain, Vinay; Kinha, Yogesh; Saharan, Sachin; Rani, Pooja (Journal of Neonatal Surgery, 2025)
All over the world, Cancer is the most fatal disease. Various forms of cancer can be treated with a variety of medication groups. The leaves extract of Wild carrot was used in this study to formulate Copper nanoparticles utilizing a Green synthetic method. NPS were successfully synthesized using the Copper Sulphate Solution as the precursor of copper and leaf extract Wild carrot of the 50 ml (5 mm) of CuSO4 was stimulated to react using the plant extracts. The nanoparticles exhibited a cuboidal shape and had an average size of 36.7nm, 53.5nm and 75.6 nm. FTIR spectrum analysis shows absorption peak of copper nanoparticles bonding among 1509-3917cm-1. In the SEM, the particle shape was found to be Cuboidal. The results showed that the copper nanoparticles demonstrated significant anticancer potential with a GI50 value of >80ug/ml of plant and copper nanoparticles. As compare to standard drug with a GI50 value of <10ug/ml a strong inhibitory effect on the cancer cells.